Mexico : Infrastructure Public Expenditure Review (IPER) - World Bank (Washington, DC, 2012)
This Infrastructure Public Expenditure Review presents options for addressing infrastructure services needs in Mexico, including (a) improvements in program design and budget allocations, (b) efficiency gains in service provision, and (c) increased private sector participation and financing in a manner consistent with the government's goals for economic growth, and within its fiscal constraints. Three infrastructure sectors-water supply and sanitation, transport, and electricity have been selected for inclusion. The study is structured in five interrelated chapters: Chapter 1 presents an overview of the infrastructure sectors-agencies and aggregate Spending. Chapter 2 reviews the levels of spending on the selected infrastructure sectors in Mexico, and existing cost-recovery mechanisms, and the related outcomes: quality and efficiency of service, and extent of coverage being offered. To explain these outcomes, Chapter 3 analyzes the processes of planning, spending allocation, and coordination within and across sub-sectors. The role of local governments and the nature of incentives they face are also discussed. Chapter 4 discusses the effectiveness of the existing programs in Mexico to encourage private participation and financing in the selected infrastructure sectors. The challenges for infrastructure development will require new and different uses of private sector financing and operations, and refined credit enhancement schemes to attract financiers, investors, and operators to Mexico's infrastructure market, without placing unwarranted contingent liabilities on the government. Chapter 5 presents a series of conclusions and recommendations to improve the efficacy of Government's interventions in the provision and financing of infrastructure.